Sharia-Based Family Financial Management Training in Aceh Jaya Regency - Riyaldi, Muhammad Haris; Umuri, Khairil; Sartiyah, Sartiyah; Syahrizal, Teuku Muhammad; Sitepu, Novi Indriyani; Nurlina, Eka; Nurdin, Ridwan; Syahriyal, Syahriyal; ZT, Fitrah Afandi; Sari, Nurma (Universitas Syiah Kuala, 2024)
This community service aims to provide Sharia-based family finance socialization for women in Aceh Jaya Regency, Aceh. This activity was motivated by the low literacy level regarding Sharia-based family financial management in Aceh Province, especially among women. So, the service activities aim to increase understanding of Sharia-based family financial management, especially among women in Aceh Jaya Regency, Aceh Province. Service activities include preparation for activities, implementation of activities, and evaluation of activities. Implementing activities are planned in coordination with the Dinas Pemberdayaan Masyarakat, Perempuan, dan Keluarga Berencana (DPMPKB) Aceh Jaya regarding availability, location, and activity participants. Activities were carried out involving women in Aceh Jaya Regency, Aceh. The Sharia-based family financial management material is delivered through discussions and questions and answers. Evaluation of the implementation of service activities is reflected in the presence and enthusiasm of participants in listening to the material presented. Community service activities provide positive results by increasing participants' understanding of Sharia-based family financial management.